Uncovering the sources of sectoral employment fluctuations - Bryn Battersby; Michael Kouparitsas; Josiah Munro (The Australian Government, The Treasury, 2013)
This paper explores the sources of fluctuations in sectoral employment growth rates across the Australian economy over three different periods: the pre-terms of trade boom period; the pre-GFC phase of the terms of trade boom; and the GFC and post-GFC phase. We find that common cyclical fluctuations, not just sector specific shocks, can and do have an important effect on sectoral growth rate dispersion across the full sample. We also find that there is evidence of accelerated structural change in the latter phase of the terms of trade boom.
Keywords: E24; E32; C51; 330; Kalman-filter; unobserved components; sectoral employment